A Glimpse of Transnationalism and biculturalism in Kazuo Ishiguro’s When We Were Orphans (International Journal of Food and Nutritional Sciences, 2022)
This article tries to examines the issue related to Transnationalism and Cultural Diversity in Kazuo Ishiguro’s works. Kazuo Ishiguro is widely known writer of translated and published works of Anglo-Japanese literature. He not only crossed the border of a nation, language but also genre. He has made his life more comfortable in various nation. Now Ishiguro has become as one of the most famous international writers of this age. He has been awarded the Nobel Prize in Literature in 2017 for his literary contribution.